The influence of hot and cool executive function on the development of eating styles related to overweight in children. (1st April 2015) - Groppe, Karoline; Elsner, Birgit
Highlights: Hot and cool EF affects 1-year development of eating behavior in 6- to 11-year-olds. Hot and cool EF shows differential effects on eating styles, mainly in girls. Lower EF predicts a stronger increase in food approach and avoidance eating styles. EF appears to be a risk factor in the development of over- and underweight. Abstract: Studies linking executive function (EF) and overweight suggest that a broad range of executive functions might influence weight via obesity-related behaviors, such as particular eating styles. Currently, however, longitudinal studies investigating this assumption in children are rare. We hypothesized that lower hot and cool EF predicts a stronger increase in eating styles related to greater weight gain (food approach) and a weaker increase in eating styles related to less weight gain (food avoidance) over a 1-year period. Hot (delay of gratification, affective decision-making) and cool (attention shifting, inhibition, working memory updating) EF was assessed experimentally in a sample of 1657 elementary-school children (German school classes 1–3) at two time points, approximately one year apart. The children's food-approach and food-avoidance behavior was rated mainly via parent questionnaires at both time points. As expected, lower levels of hot and cool EF predicted a stronger increase in several food-approach eating styles across a 1-year period, mainly in girls. Unexpectedly, poorer performance on the affective decision-making task also predicted an increase in certain food-avoidance styles, namely, slowness in eating and satiety responsiveness, in girls. Results implicate that lower EF is not only seen in eating-disordered or obese individuals but also acts as a risk factor for an increase in particular eating styles that play a role in the development of weight problems in children.